Experimental Study on the Influence of Water and Cavitation on Propeller Load during Ice-Propeller Milling - Pei Xu; Chao Wang; Liyu Ye (Applied Sciences, 2021)
When the ice-class propeller sails in an icy sea, it is affected by external factors such as water, ice, and cavitation, and the process of mutual interference is extremely complicated. In order to study the influence of water and cavitation on propeller load during the ice-propeller milling process, a test platform for ice–water propeller milling action was constructed. The load and cavitation of the propeller and single blade were measured during ice-propeller milling in air and water (atmospheric pressure and decompression conditions). Simultaneously, the changes in the load and bearing force of the propeller and blade were studied at different working conditions. The results show that, in the process of ice–water propeller milling, the direction of the propeller thrust generated by the water is opposite to that of the axial force generated by ice; the combined action of the two causes propeller thrust loss, whereas the combined action of water and ice increases propeller torque. The presence of water increases the thrust, torque, and bearing force of the fluctuating amplitude of the blade. The occurrence of cavitation reduces the thrust and torque of the propeller and blade and increases thrust fluctuating amplitudes while decreasing the tangential force fluctuating amplitude of the blade.